The Position Of Proof Of Suspicion In Determining The Status Of Out-Of-Wedlock Children As Biological Children - Sadjeli, Siti Soraya; Ramadhani, Dwi Aryanti (UNIVERSITAS PAKUAN, 2025)
Abstract This study aims to examine the position of evidence of suspicion as stipulated in Article 1915 of the Civil Code, especially proof to determine the status of out-of-wedlock children as biological children in civil procedure law, and to explore the extent to which the legal system provides protection for the civil rights of out-of-wedlock children who are determined as biological children without a DNA test. The type of research used is normative juridical which is descriptive-analytical, using a legislative approach and a case approach, with data collection techniques through literature studies, and processing qualitatively analyzed data. The results of the study show that evidence of suspicion is legal according to the law and can be used as a basis for judge's consideration if it is supported by the facts. A civil relationship between a child and a biological father can be recognized without a DNA test, simply with other evidence such as communications, witnesses, or indirect confessions at trial. This ensures the child's access to custody, identity, education, inheritance, and alimony. The state plays a role in protecting the rights of children out of wedlock in an inclusive manner and eliminating birth status discrimination. Suspect evidence needs to be strengthened as an alternative to proof if a DNA test is not carried out. The judge is expected to assess indirect facts wisely for the best interests of the child. Regulation, socialization, and training of law enforcement are needed to ensure that proof without DNA tests guarantees the protection of the civil rights of out-of-wedlock children. Keywords: Evidence of Suspicion, Status of Out-of-wedlock Children, Civil Procedure Law, Civil Rights.